Arabic for dummies - Bouchentouf, Amine (Hoboken, N.J. : Wiley, 2013)
Written by a native Arabic speaker, this guide takes a straightforward and practical approach to this complex language.
Introduction -- Getting started -- Arabic in action -- Arabic on the go -- The part of tens.
Includes CD-ROM.
Includes index.
Written by a native Arabic speaker, this guide takes a straightforward and practical approach to this complex language.
Book is accompanied by one cd entitled' Arabic for dummies' bearing the same call number and available at Koleksi Media.
Keywords: Arabic language -- Textbooks for foreign speakers -- English; Arabic language -- Self-instruction.